Topical 3D modelling and simulation of air dispersion hazards as a new paradigm to support emergency preparedness and response. (September 2021) - Armand, Patrick; Oldrini, Olivier; Duchenne, Christophe; Perdriel, Sylvie
Abstract: Releases into the atmosphere resulting from accidents or malicious activities may be extremely diverse in nature and have harmful consequences for human health and the environment. Successfully managing such releases is a matter of the utmost importance for security services and governmental authorities. For some decades, Atmospheric Transport and Dispersion (AT&D) models embedded in Decision-Support Systems (DSS) have been operated in order to simulate the space and time distribution of hazardous materials and to assess their health impact on the population and on first responders in cases of emergency. Unfortunately, the AT&D models in DSS generally oversimplify the local or regional environment and are compromised by insufficient space and time resolution close to the source of the release. Thus, we have developed a DSS based on 3D multi-scale weather forecast and Lagrangian AT&D models in the frame of a project called "EMERGENCIES". As an emblematic example, we have performed dispersion simulations of fictitious noxious releases from the inside or outside of public buildings both at micro-scale in a very large domain encompassing the city of Paris and its suburbs, and at meso-scale beyond this domain. Furthermore, results have been produced in a time lapse consistent with emergency management thanks to large, yet affordable computational resources. Providing emergency response actors with such operational, accurate and reliable results may be extremely advantageous for both preparedness and response to emergencies. Ultimately, state-of-the-science AT&D models offer a sound validated new paradigm to support decision-making by security services and their authorities facing contingent Chemical, Biological, Radioactive, Nuclear or Explosive (CBRN-E) releases into the air. Graphical abstract: Example of visualizations in the EMERGENCIES project. The large view is a 2D section of the plumes over the entire city of Paris, 2 h after the beginning of the first release. The vignettes are oblique zooms of the plumes in the museum district (bottom left-hand side) and in the administrative building (bottom right-hand side), 20 min after the start of the fictitious releases in these two areas. The green (respectively orange) tint corresponds to low (respectively high) concentrations of the released substance. Image 1 Highlights: Decision-Support Systems (DSS) can be of high interest for emergency response actors. Atmospheric Transport and Dispersion (AT&D) models in DSS are often oversimplified. The EMERGENCIES project used 3D multi-scale high resolution AT&D modelling. The results produced in the EMERGENCIES project were timely, accurate and reliable. Up-to-date AT&D models are the new paradigm of emergency preparedness and response.